Early onset of depression and treatment outcome in patients with major depressive disorder. (July 2021) - Herzog, David P.; Wagner, Stefanie; Engelmann, Jan; Treccani, Giulia; Dreimüller, Nadine; Müller, Marianne B.; Tadic, André; Murck, Harald; Lieb, Klaus
Abstract: Major depressive disorder (MDD) is a highly heterogeneous disorder, which may partly explain why treatment outcome using antidepressants is unsatisfactory. We investigated the onset of depression as a possible clinical marker for therapy response prediction in the context of somatic biomarkers blood pressure and plasma electrolyte concentration. 889 MDD patients were divided into early (EO, n = 226), intermediate (IO, n = 493), and late onset (LO, n = 169) patients and were analyzed for differences in socio-demographic and clinical parameters, comorbidities and treatment outcome as well as systolic blood pressure and electrolytes. EO patients more often suffered from a recurrent depression, had more previous depressive episodes, a higher rate of comorbid axis I and II disorders, and more often reported of suicidality (p < 0.001) compared to IO and LO patients. Treatment outcome was not different from IO and LO patients, although LO patients responded faster. EO patients who showed an early non-improvement of depression after 2 weeks of therapy (<20% improvement) had a 4.3-fold higher likelihood to become non-remitter as compared to LO patients with an early improvement. EO patients had significantly lower systolic blood pressure than patients with IO or LO and electrolytes in EO patients were significantly correlated with depression severity. Our results confirm other studies showing an association of an early onset of depression with a slower treatment response. The worse treatment outcome in patients with an additional early non-improvement to antidepressant therapy opens perspectives to develop and test individualized treatment approaches for EO and LO patients in the future, which may be based on differences in autonomic regulation.